A remarkable fossil leptosaldine bug from Mid-Cretaceous Burmese amber (Hemiptera: Heteroptera: Leptopodomorpha: Leptopodidae) - Popov, Yuri A.; Heiss, Ernst (Zootaxa, 2016)
A new genus and species of leptosaldine bugs, Leptosaldinea cobbeni gen. et sp. nov. (Hemiptera: Heteroptera: Leptopodidae) is described and illustrated from Burmese Middle Cretaceous (Albian-Cenomanian) amber found in Kachin State, northern Myanmar. This is the third record of a leptosaldine bug from Burmese amber. A brief analysis of the characters and systematic relationships of Leptosaldinae is provided.